The Influence of Principal Leadership and Work Motivation to Teachers Performance at Elementary School In District Samarinda Ilir Samarinda Year 2017 - Nur Agus Salim (PENDAS MAHAKAM: Jurnal Pendidikan dan Pembelajaran Sekolah Dasar, 2018)
This study aims to determine the influence of leadership of the Principal with the performance of teachers, the influence of teacher work motivation with teacher performance, the influence of leadership of Principal and teacher work motivation together with teacher performance. The population of this research is 90 elementary school teachers in 9 primary schools. Given the population is limited then this study is a population study where the sample research is the entire population of teachers in the State Elementary School Samarinda Ilir. The research method used quantitative method with regression analysis. The result of descriptive analysis revealed that the performance of teacher of majority in medium category that is equal to 63%, majority of headmaster leadership in medium category that is equal to 71%, and at work motivation of majority teacher in medium category that is equal to 69,6%. So that is so descriptively both teacher performance, Principal leadership and teacher work motivation is in medium category. The results of the study found that: (a) there was influence of Headmaster Leader's variables (X1) with teacher performance variable (Y) at the strong closeness level, that is 0,749 with coefficient determination 0,561, and regression equation Ŷ = 67,402 +0,456 X1 (b ) There is influence of teacher work motivation variable (X2) with teacher performance variable (Y) at moderate level, that is 0,749 with coefficient determination 0,561, and regression equation Ŷ = 60,734 + 0,572X2 (C) there is influence of leadership variable of Principal (X1) and teacher work motivation variable (X2) together with teacher performance variable (Y) at strong level of closeness, that is equal to 0,774 with coefficient determination 0,600 and regression equation Ŷ = 57,299 + 0.340 X1 + 0.236X2. The conclusion of this research is that improving the performance of elementary school teachers in Samarinda Ilir can be done by improving principal leadership and teacher work motivation.